Reaction of potato varieties to treatment with nitrogen-fixing bacteria and mycorrhizal biopreparations - Vladyslav Kovalenko; Pavlo Serdiuk; Arthur Shevych; Oleksandr Serdiuk; Viktor Zakorko (Наукові горизонти)
The commercial value of potato plants for tuber production is substantial enough to explore ways to reduce the cost of the final product by optimising largescale cultivation systems. Treating tubers with biological products makes it possible to reduce the use of phosphorus fertilisers and shorten the growing season. Furthermore, high-quality and commercially viable plant material can be produced by introducing beneficial microbiota. The objectives of this study were to determine the level of genetic potential realisation in early potato varieties when biologically active substances are used in tuber treatment, to identify the maximum achievable potential of the varieties examined, and to diagnose early potato forms. Regarding plant mineral nutrition, mycorrhizal fungi biological preparations represent one of the most important groups of soil microflora and could be applied in agricultural inoculation practices. The results obtained for starch content in the examined potato varieties indicated that treatment with biological preparations had no significant influence on its levels in tubers. However, a positive trend was observed in the dry matter content in almost all tuber treatment variants using biopreparations. The reaction of varieties to the average weight of marketable and individual tubers demonstrated the effectiveness of the preparations in enhancing key marketability indicators across all experimental variants. Treatment with biological preparations does not address the issue of providing all microelements during the potato vegetation period. Therefore, elements like boron should be incorporated into planning an optimal nutrition system